My Son Wears Heels One Mom's Journey from Clueless to Kickass - Tarney, Julie (The University of Wisconsin Press, 2016)
In 1992, Julie Tarney's only child, Harry, told her, "Inside my head I'm a girl." He was two years old. Julie had no idea what that meant. She felt disoriented. Wasn't it her role to encourage and support her child? Surely, she had to set some limits to his self-expression-or did she? Would he be bullied? Could she do the right thing? What was the right thing? The internet was no help, because there was no internet. And there were zero books for a mom scrambling to understand a toddler who had definite ideas about his gender, regardless of how Nature had endowed him. Terms such as transgender, gender nonconforming, and gender creative were rare or nonexistent. There were, however, mainstream experts who theorized that a "sissy" boy was the result of a domineering mother. Julie couldn't believe it. She didn't want to care what her neighbors thought, but she did care. "Domineering mother" meant controlling mother. It meant bad mother. It meant her mother. Lacking a positive role model of her own, and fearful of being judged as a mom who was making her son "too feminine," Julie embarked on an unexpected parenting path. Despite some missteps, and with no map to guide her, she learned to rely on her instincts. She listened carefully, kept an open mind, and as long as Harry was happy, she let him lead the way. Julie eventually realized that Harry knew who he was all along. Her job was simply to love and support him unconditionally, allowing him to be his authentic self. This story of a mother embracing her child's uniqueness and her own will resonate with all families.